Sudden death in a case of sickle cell anemia: post-mortem computed tomography and autopsy correlation from a radiologist's perspective - Abdul Rashid, Saiful Nizam; Krauskopf, Astrid; Vonlanthen, Bruno; Thali, Michael J.; Ruder, Thomas D. (Elsevier, 2013)
Sickle cell anemia (SCA) is a hemolytic disease characterized by the production of abnormal hemoglobin chains and distorted red blood cell morphology or sickling. "Sickle cell crisis" includes vaso-occlusive crisis, a plastic crisis, sequestration crisis, haemolytic crisis and often culminating in serious complications, organ damage and even sudden death. Post-mortem computed tomography (PMCT) findings of sickle cell disease have never been reported in literature. This case of sudden death from acute hemolytic crisis in SCA where post-mortem computed tomography (PMCT) and autopsy findings complemented each other, both revealing findings invisible to the other and both crucial to the case.